Analysis of the dynamic response of a ring resonator to a time-varying input signal - Kalli, Kyriacos; Jackson, David A. (My University, 1993)
This paper describes an experimental and theoretical study of the response of an all-fiber ring resonator spectrometer for input with time-varying signal. It is shown that an extremely high optical resolution complicates the optical output. Reducing the response time by reducing the ring length lowers the spectrum distortion at the cost of absolute resolution.
Keywords: Fiber optics; Mathematical models; Resonators; Phase modulation